Primary percutanous coronary intervention in acute myocardial infarction : A single center experience - Mayali, Ahmed (Karbala Journal of Medicine, 2019)
Abstract Background: Early revascularization is critically important in the management of patients presenting with acute myocardial infarction. Aim: To assess the benefit of delayed in comparison with early primary percutaneous coronary intervention in patients with acute ST elevation myocardial infarction. Methods: This prospective study include 51patients with acute STEMI they were selected from those who had admitted to the coronary care unit of Karbala cardiac center in Karbala-Iraq during a period between january 2017 and february 2018. Detailed history and thorough physical examinationwas done. Investigations done for each patient in form of ECG, cardiac troponin, , blood urea, serum creatinine, and complete blood picture. Results & discussion: PTCA only, using one stent, two stent, three stent , aspiration catheter, CABG & medical treatment, 7 (13.7%), 25(49%), 8(15.6%), none , 4(7.8%), 4(7.8%) , 4(7.8%), 3(5.8%) respectively). infarct related artery, LAD, LCX, RCA & LMS (30(58.8%), 4(7.8%), 6(11.7%), 2(3,9%) respectively, and the number of diseased vessels , single vessel, two vessels, three vessels & LMS which was (20(39.2%), 13(25.4%), 14(27.4%) respectively inhospital outcome, which include the following:- favorable outcome, period of hospitalization, access site bleeding, contrast induced nephropathy, death, respectively. which were (96%, ˂ 1day 38(74.5%), ˃1day 13(25.5) , 3.9%, 5.8%, 3.9% respectively) conclusion: in case of ST elevation myocardial infarction, left anterior descending artery is most culprit vessel to be involved, one quarter of patient needs one stent & carry favorable out comes in form of less complications and also decrease the period of hospitalization.